2019
DOI: 10.1590/1980-549720190006.supl.2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de diabetes mellitus determinada pela hemoglobina glicada na população adulta brasileira, Pesquisa Nacional de Saúde

Abstract: RESUMO: Objetivo: Analisar as prevalências de diabetes mellitus segundo diferentes critérios diagnósticos, na população adulta brasileira, segundo os resultados laboratoriais da Pesquisa Nacional de Saúde. Métodos: Análise dos dados laboratoriais da Pesquisa Nacional de Saúde, coletados entre os anos de 2014 e 2015. Foram calculadas as prevalências de diabetes conforme diferentes critérios diagnósticos. Foram calculadas as prevalências de diabetes segundo o critério de hemoglobina glicosilada ≥ 6,5% ou em … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
45

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 24 publications
2
24
0
45
Order By: Relevance
“…Studies with laboratory data allow estimating the prevalence of health problems in subclinical stages and populations with less access to health services, and therefore, still without diagnosis and treatment. For example, recent studies with PNS laboratory data have already shown a high prevalence of chronic renal failure 30 and diabetes 15 , compared to self-reported measures. The most prevalent MetS components were high WC followed by low HDL cholesterol in both genders, but with higher prevalence among women and any age group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies with laboratory data allow estimating the prevalence of health problems in subclinical stages and populations with less access to health services, and therefore, still without diagnosis and treatment. For example, recent studies with PNS laboratory data have already shown a high prevalence of chronic renal failure 30 and diabetes 15 , compared to self-reported measures. The most prevalent MetS components were high WC followed by low HDL cholesterol in both genders, but with higher prevalence among women and any age group.…”
Section: Discussionmentioning
confidence: 99%
“…The National Health Survey carried out in 2013 was a nationwide home-based survey developed in a partnership between the Ministry of Health, the Oswaldo Cruz Foundation (Fiocruz), and the Brazilian Institute of Geography and Statistics (IBGE). The PNS sample was selected by clusters in three stages through simple random sampling: census tracts, a fixed number of private households, and a resident aged 18 years or older were selected for each household, with an equiprobability of selection among individuals residing in the same household, to answer the individual questionnaire 15,16 . A total of 81,167 households was visited, of which 69,994 had residents 16 .…”
Section: Design and Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…As prevalências de hipertensão, diabetes e obesidade foram obtidas da Pesquisa Nacional de Saúde (PNS) de 2013, o mais recente inquérito populacional brasileiro representativo com adultos (18 anos ou mais de idade) que inclui medidas antropométricas, aferição da pressão arterial e coleta de material biológico (sangue e urina) para análises laboratoriais (7,8,32).…”
Section: Prevalências Dos Fatores De Riscounclassified
“…É provável que esses aumentos na prevalência de diabetes decorram do já estabelecido aumento na prevalência de obesidade no Brasil (36) . Além disso, indivíduos com excesso de peso apresentam grau de anormalidade da homeostase glicêmica (diabetes ou glicemia de jejum alterada) mais elevada do que aqueles com peso adequado.…”
Section: Estudos Epidemiológicos Como Nurses' Health Study Nhanes unclassified